PRODUKSI TELUR ITIK MOJOSARI DENGAN PEMBERIAN PAKAN CAMPURAN KEONG SAWAH - Daro Ngga?a, Maria Diana; Supartini, Nonok; Suroto, Karunia Setyowati (Fakultas Pertanian, 2017)
The aim of this research is to determike feeding to mojosari duck egg production and to give alternative duck feed. This study used a complete randomized design (RAL) method consisting of 7 treatments ie A0B0, A0B1, A0B2, A0B3, A1B1, A1B2, A1B3 and each treatment was repeated 3 times so that there were 21 experimental units. The material used is the female, with the age of 6-7 months, as many as 30kor that match the research criteria of the same maintenance and hatching, the same weight with an average of 1.6kg. This study used 7 treatments: A0B0: using 100% bran, A0B1: Without using rice aking rice + rice snail 25%, A0B2: without using rice rice aking rice + 35% rice snail, A0B3: without using rice rice + 45% rice snail, A1B1: using Rice aking rice + rice snail 25%, A1B2: aking rice user + rice field snail 35%. The results of this study indicate that fresh feed consumption gives a very real effect (P